Dietary Supplementation With ω6 LC-PUFA-Rich Algae Modulates Zebrafish Immune Function and Improves Resistance to Streptococcal Infection - Nayak, Sagar; Khozin-Goldberg, Inna; Cohen, Guy; Zilberg, Dina (Frontiers in Immunology, 2018)
Arachidonic acid (ARA, 20:4n-6) and dihomo-γ-linolenic acid (DGLA, 20:3n-6) are omega-6 long-chain polyunsaturated fatty acids (LC-PUFA), which are key precursors for lipid mediators of the immune system and inflammatory response. The microalga Lobosphaera incisa (WT) and its Δ5-desaturase mutant P127 (MUT) are unique photosynthetic sources for ARA and DGLA, respectively. This study explores the effect of dietary supplementation with L. incisa and P127 biomass on tissue fatty acid composition, immune function and disease resistance in zebrafish (Danio rerio). The broken microalgal biomass was added to commercial fish feed at 7.5 and 15% (w/w), providing 21.8 mg/g feed ARA for the WT-supplemented group and 13.6 mg/g feed DGLA for the MUT-supplemented group at the 15% inclusion levels. An unsupplemented group was used as the control. After one month of feeding, fish were challenged with Streptococcus iniae. Fish were sampled before the challenge and one week after the challenge for various analyses. Tissue ARA and DGLA levels significantly increased in the liver, corresponding to microalgal supplementation levels. The elevated expression of specific immune-related genes was evident in the kidneys in all treatment groups after one month of feeding, including genes related to eicosanoid synthesis, lysozyme, and NF-κB. In the liver, microalgal supplementation led to the upregulation of genes related to immune function and antioxidant defense while the expression of examined genes involved in ARA metabolism was downregulated. Importantly, fish fed with 15% of both WT- and MUT-supplemented feed showed significantly (p < 0.05) higher survival percentages (78% and 68%, respectively, as compared to only 46% in the control group). The elevated expression of genes related to inflammatory and immune responses was evident post-challenge. Collectively, the results of the current study demonstrate the potential of microalgae-derived dietary ARA and DGLA in improving immune competence and resistance to bacterial infection in zebrafish as a model organism.